(3GdLhGgQ GdeVjI aj WHbGJ GdMfajIs - (3YHO GdbGOQ Hf eMeO Hf eMeO Hf fUQGddg Hf SGde eMjj GdOjf CHi eMeO GdeYQha HGHf CHi GdhaGA GdbQTi GdJejei GdeUQj GdMfaj,J (B775 (3g` s
(3ChdgG (B:s
(3GdMeO hGdYXeI hGdcHQjGA def dg GdCSeGA GdMSfi s
(3BNQgG (B:s
(3gPG BNQ cJGH GdLhGgQ bO Je HMeO Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B42s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B80 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B11 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B616s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs